(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
As an academic subject, a second foreign language is gaining more and more popularity, which, of course, is associated with the social need for multilingual education of members of society. It is introduced in many types of educational institutions: in schools with a basic course of teaching a foreign language, in schools with its in-depth study, in gymnasiums, colleges, lyceums, higher educational institutions. This article highlights theoretical and practical aspects of forming students’ speech in French based on a creative approach.